Anthropometric record to be used in Centers for Family Health Support: possibilities and obstacles - Camila Fabiana Rossi Squarcini; Gilmar Mercês de Jesus; Edio Luiz Petroski (Universidade Federal de Santa Catarina, 2015)
A model of an anthropometric record to be used in the Núcleos de Apoio à Saúde da Família (Centers for Family Health Support) in Brazil has been proposed in the literature, showing the logistics of use. The aim of this study was to discuss the anthropometric record, showing the potential and obstacles of its use. It was observed that, for adults, the screening measures (body mass index and waist circumference) for the determination of the risk of cardiovascular and metabolic diseases can be considered promising, although the Basic Health Care network already uses these measures. Nevertheless, the supplementary assessment (skinfold thickness and body circumferences) could be another potential possibility, except for the time spent to perform this assessment and the lack of studies of the cost-benefit of these anthropometric techniques. It was concluded that the anthropometric record proposed is an important instrument for improving the quality of the service provided to users of the Basic Health Care System; however, some adjustments, such as the removal of skinfold measurements as part of primary care, should be taken into consideration.